2021
DOI: 10.3390/ijms22115908
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Specific Ablation of CXCL12 in Mice Downregulates CXCR7 Associated with Defective Coronary Arteries and Cardiac Hypertrophy

Abstract: The chemokine CXCL12 plays a fundamental role in cardiovascular development, cell trafficking, and myocardial repair. Human genome-wide association studies even have identified novel loci downstream of the CXCL12 gene locus associated with coronary artery disease and myocardial infarction. Nevertheless, cell and tissue specific effects of CXCL12 are barely understood. Since we detected high expression of CXCL12 in smooth muscle (SM) cells, we generated a SM22-alpha-Cre driven mouse model to ablate CXCL12 (SM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…At several stages, we confirmed specificity of the reporter using immunohistochemistry (IHC) for DsRed reporter expression and markers for endothelium including ETS related gene (ERG) and endomucin (EMCN). As in other organ systems, Cxcl12-DsRed is expressed highly throughout the arterial endothelium with additional expression observed in vascular smooth muscle cells (VSMCs) (Fig S1A-F) (Chang et al, 2017;Ghadge et al, 2021;Ivins et al, 2015;Takabatake et al, 2009). We observed no DsRed expression in vein endothelium during these developmental time periods.…”
Section: Morphometric Analysis Of the Developing Pulmonary Arterial S...supporting
confidence: 68%
“…At several stages, we confirmed specificity of the reporter using immunohistochemistry (IHC) for DsRed reporter expression and markers for endothelium including ETS related gene (ERG) and endomucin (EMCN). As in other organ systems, Cxcl12-DsRed is expressed highly throughout the arterial endothelium with additional expression observed in vascular smooth muscle cells (VSMCs) (Fig S1A-F) (Chang et al, 2017;Ghadge et al, 2021;Ivins et al, 2015;Takabatake et al, 2009). We observed no DsRed expression in vein endothelium during these developmental time periods.…”
Section: Morphometric Analysis Of the Developing Pulmonary Arterial S...supporting
confidence: 68%
“…Interestingly, this phenotype was associated with downregulation of ACKR3 expression in coronary artery endothelial cells, indicating an important role of ACKR3 in vessel maturation and cardiac remodelling. Furthermore, treatment of these mice with ACKR3 agonist TC14012 attenuated these defects and restored cardiac function with a marked activation of pERK signalling, suggesting that activation of pERK signalling pathways induced by the binding of TC14012 to ACKR3 prevented the progression of cardiac hypertrophy ( 67 ) ( Figure 1 ).…”
Section: Ackr3 In Cardiovascular Diseasesmentioning
confidence: 98%
“…More recently, conditional smooth muscle specific deficiency of Cxcl12 (SM22CRE- Cxcl12 flox/flox ) revealed that CXCL12 was involved in cardiac and vascular homeostasis by regulating ACKR3 expression and its signalling. Indeed, in these mice, a high embryonic lethality characterized by developmental defects of the cardiovascular system was observed concomitant with alterations of coronary arteries structure ( 67 ). Adult mice developed cardiac hypertrophy and severe vascular defects associated with increased fibrosis, apoptosis and dilated arteries with thinner walls leading to impaired cardiac function.…”
Section: Ackr3 In Cardiovascular Diseasesmentioning
confidence: 99%
“…However, pharmacological targeting of ACKR3/CXCR7 by administration of CXCR7-agonist TC14012 retards cardiac hypertrophy in these mice, suggesting its therapeutic efficacy in counteracting adverse remodeling. TC14012-treated SM22α-Cre + CXCL12 f/f mice also show improvements in LVEF [ 132 ].…”
Section: Therapeutic Implication Of Ackr3/cxcr7 In Platelet-associated Cardiovascular Diseasementioning
confidence: 99%